(untitled) (KYAMC Journal, 2024)
Background: Homicide is regarded as a notorious crime against the society that causes intentional killing, aggravated assaults resulting in death. Nowadays, the incidence of homicide is increasing worldwide and it is a matter of great concern all over the world and it has significant consequence for both social and economic security of the people as well as national development. Objective: This study was aimed to describe the pattern homicidal behavior and the relationships among socio-demographic characteristics. Materials and Methods: A record-based retrospective cross-sectional study includes 180 cases of homicide out of the total of 1296 medico-legal autopsies conducted at Forensic Medicine Department of Dhaka Medical College during the year from July 2021 to June 2022. Results: A total number of 1296 medico-legal autopsies were conducted, of them 180(13.89%) cases were homicide and others (RTA, suicide, fall from height, poisoning, hanging, burn) were 1116(86.11%). Out of 180 homicidal death, most of them were 30-40 age group 66(36.67%), 144 cases were male (80 %) and 36 were female (20 %) whereas considering religion, the majority were Muslim 156 in number (86.67%) and the rest were of other religion. Among the homicidal death married were 150 (83.33%), in case of occupation most of them were Jobholder 39 (21.67%). According to the method of homicide, stab wound was the favorite homicide method used over victims 60(33.33%), 36(20%) cases were chop, 30(16.67%) cases were gunshot & strangulation and 24(13.33%) cases were others causes. Regarding place of residence of most of them were from Shahbag thana 108(60%). Conclusion: Stab wound was the favorite homicide method in Bangladesh and the most common age of the victims were 30-40 age group. The usefulness of the data in the scientific community is the database of homicide that should be advantageous for pathologists and forensic scientists work and particularly to be a guideline for homicide investigations in Bangladesh. KYAMC Journal Volume: 15, No: 01, April 2024: 25-28.